The Use of English Songs to Improve the Listening Comprehension of Eighth-Grade Students at SMP Negeri 2 Babahrot - Annisaa, Annisaa; Efendi, Zuhri (Action Research Literate, 2024)
English is the world's international language of communication. In some countries, English is even a common language or mother tongue. This study aims to determine the effectiveness of using English songs in improving students' listening skills. The population of this study is VIII-grade students at SMP Negeri 2 Babahrot. The study involved two groups: experimental group that learned by using songs and control group that used traditional teaching methods. The experimental group, consisting of 23 students, took a pretest and a posttest to measure the impact of the learning intervention using songs on their listening ability. The comparison between the two groups showed that the experimental group showed greater improvements in English language skills compared to the control group, with a mean pretest score of 60.70 and posttest score of 74.43. The use of English songs significantly improved the listening skills of the grade VIII students. These results support the hypothesis that using songs into English language learning, especially in improving listening skills, can improve students' listen skills. This suggests that songs can be an effective strategy for improving students and used as additional materials to increase students' motivation and engagement in learning.